Effective Marketing System for Fine Art Artist in Indonesia - Larasati, Widya; Hudrasyah, Herry (Journal of Business and Management, 2015)
The research of Ã¢â‚¬Å“Effective Marketing System for Fine Art Artist in IndonesiaÃ¢â‚¬Â aims to give recommendation about the effective marketing system for fine art artist in Indonesia since a lot of Indonesian fine art artists do not have and use effective marketing system when market their artwork to the market. The empirical part of this study was conducted in June 2015 in Jakarta and Bandung area. The subject of this study were Indonesian fine art artists and gallery/art management and the research was done by using narrative analysis. This type of analysis produces strategies to inform the conduct, interpretation and presentation of interview talk, and encourages and enables researcher to take account of research participantsÃ¢â‚¬â„¢ own evaluations (Janine L Wiles et.al, 2004), which is very suitable with the conducted data collection method. On the basis of the result of this research, it is proved that Indonesian fine art artists do meet some difficulties especially because they do not have proper knowledge about artwork pricing system and marketing. The study resulted that understand marketÃ¢â‚¬â„¢s need and social media usage are the effective marketing for Indonesian fine art artist. The study offers all Indonesian fine art artist an effective marketing system, which hopefully can help them in building better art appreciation in the market and make more contribution to IndonesiaÃ¢â‚¬â„¢s economy.Ã‚Â Keywords:Fine Art Artist, Effective Marketing, Marketing System, Indonesia